Heavy Metal Concentration in Tannery Solid Wastes Used as Poultry Feed and The Ecotoxicological Consequences (Bangladesh Journal of Scientific and Industrial Research, 2008)
In Bangladesh, the tannery solid wastes are converted to protein-concentrate to be used as poultry feed, fish feed, and in production of organic fertilizers. Over the last several years it is a common phenomenon in the largest tanning area of the country, the Hazaribagh tannery area at the south-east part of Dhaka city. One of the major concerns of these activities is the heavy metals, especially chromium, used in the tanning processes. A total of 18 samples were collected to study the heavy metal status of protein-concentrate production in the tanning area at various stages from the source to the final product, and to compare this with the imported ones. The various types of solid waste processing for protein-concentrate production were covered in sampling, and along with the heavy metal status these processes were studied comprehensively. The maximum chromium content of the solid waste was found to be 3.2 %. The final products sampled at two different places contained as high as 2.49 % and 1.94 % chromium. Cadmium, lead, arsenic, and mercury contents of all samples were also determined. The detected maximum and minimum concentrations of these elements were found to be: 3.888 ppm and 0.991 ppm for cadmium, 30.114 ppm and 7.577 ppm for lead, 2.212 ppm and 0.099 ppm for arsenic, and 13.916 ppm and 0.166 ppm for mercury. Key words: Heavy metal, Food chain, Ecotoxicology, poultry feed. Bangladesh J. Sci. Ind. Res. 42(4), 397-416, 2007